2019
DOI: 10.1016/j.micinf.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Cognate T and B cell interaction and association of follicular helper T cells with B cell responses in Vibrio cholerae O1 infected Bangladeshi adults

Abstract: Vibrio cholerae O1 can cause life threatening diarrheal disease if left untreated. T cells can play critical roles in inducing B cell mediated immunity. As the mechanism of T cell dependent B cell maturation is not well established, we hypothesized that a specific population of T (follicular helper T, Tfh)) cells, are involved in B cell maturation following cholera. We found flowcytometrically that V. cholerae infection induces significant increases in circulating Tfh cells expressing B cell maturation associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…IL-23 is a member of a group of cytokines that stimulate naive T cells to differentiate into Th17 cells, and among this group of cytokines, IL-23 is known to further differentiate Th17 cells into T follicular helper (Tfh) cells (30). Antigen-specific Tfh cells are thought to be critical for the development of protective memory B cell responses that mediate long-term immunity, and a recent study found that circulating Tfh cells in patients with cholera affect subsequent antigen-specific B cell development and consequent immunoglobulin production (31). IL-23 stimulates Th17 cells, and we previously observed that Th17-associated cytokines are activated in cholera patients to a greater degree than in OCV recipients (3).…”
Section: Discussionmentioning
confidence: 99%
“…IL-23 is a member of a group of cytokines that stimulate naive T cells to differentiate into Th17 cells, and among this group of cytokines, IL-23 is known to further differentiate Th17 cells into T follicular helper (Tfh) cells (30). Antigen-specific Tfh cells are thought to be critical for the development of protective memory B cell responses that mediate long-term immunity, and a recent study found that circulating Tfh cells in patients with cholera affect subsequent antigen-specific B cell development and consequent immunoglobulin production (31). IL-23 stimulates Th17 cells, and we previously observed that Th17-associated cytokines are activated in cholera patients to a greater degree than in OCV recipients (3).…”
Section: Discussionmentioning
confidence: 99%
“…After V. cholerae infection, the early induction of V. cholerae -specific T follicular helper cells (Tfh) has been correlated with later memory B cell responses to the same V. cholerae antigens. In vitro, Tfh cells isolated from cholera patients induced class-switching in a B cell–Tfh coculture . Overall, it seems that T cell-mediated V. cholerae responses may contribute to V. cholerae protective immunity, potentially through T cell help or other mechanisms that are not yet understood …”
Section: Clinical Manifestations and Treatmentmentioning
confidence: 99%
“…In vitro, Tfh cells isolated from cholera patients induced class-switching in a B cell–Tfh coculture . Overall, it seems that T cell-mediated V. cholerae responses may contribute to V. cholerae protective immunity, potentially through T cell help or other mechanisms that are not yet understood …”
Section: Clinical Manifestations and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…V. cholerae infection also induces the development of circulating Tfh cells. These Tfh cells provide help to activated B cell leading to secretion class-switched antibodies by plasma cells and development of antigen-specific memory B cells ( 66 ).…”
Section: Vibrio Choleraementioning
confidence: 99%